Potentiostatic And Pulse Electrodepositon Of Copper Selenide Thin Films - Koo, Chee Siong (2009)

(untitled)
Copper selenide attracts much interest due to its potential applications in photovoltaic devices, rechargeable lithium battery, superionic conductor, ion selective microelectrode and as a precursor to prepare CuInSe2. Among the synthesis methods for copper selenide, electrodeposition is relatively simple, cost-effective, and low temperature growth technique. However, previously no detailed studies on electrodeposition parameters of this metal chalcogenide have been carried out. On the other hand, pulse electrodeposition of copper selenide has never been reported. In present work, copper selenide thin films were electrodeposited onto indium tin oxide coated glass (ITO) in acidic aqueous solution containing CuSO4 and Na2SeO3 via potentiostatic and a novel pulse technique from a three-electrode cell. The electrode processes and potential range of copper selenide deposition were studied by cyclic voltammetry. Characterisation of the films was performed using Xray Diffractometry (XRD), Photoelectrochemical Test (PEC) and Scanning Electron Microscopy (SEM). Optical band gap and transition type of the copper selenide were determined using UV-vis Spectrophotometer.